2021
DOI: 10.1186/s13690-021-00551-1
|View full text |Cite
|
Sign up to set email alerts
|

The usability of Jordan stillbirths and neonatal deaths surveillance (JSANDS) system: results of focus group discussions

Abstract: Background Jordan Stillbirths and Neonatal Deaths Surveillance system (JSANDS) is a newly developed system and is currently implemented in five large hospitals in Jordan. This study aimed at exploring the healthcare professionals’ perception about the usability of JSANDS. Methods A descriptive qualitative approach, using focus group discussions, was adopted. A total of 5 focus groups including 23 focal points were conducted in five participating ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Currently, in Jordan's HIS, the evaluation of various types of data shows that birth registrations are almost complete (99%), while death registrations represent 75%. According to Khader, Alyahya et al [8], some neonatal deaths and stillbirths are not fully registered due to a malfunctioning reporting system that places the responsibility of registration on families [9].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, in Jordan's HIS, the evaluation of various types of data shows that birth registrations are almost complete (99%), while death registrations represent 75%. According to Khader, Alyahya et al [8], some neonatal deaths and stillbirths are not fully registered due to a malfunctioning reporting system that places the responsibility of registration on families [9].…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that the users of the JSANDS found the system to be useful, functional, and high-performing. In a previous study on the usability of JSANDS, health professionals rated it positively as indicated by the high usability ratings, satisfaction with the system, and ratings of the helpfulness of the system in making important decisions with quality of care [12]. JSANDS was rated by the system users as useful because it provides estimates of the PNN mortality rate and the causes of deaths overall according to other social and clinical determinants.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the users of the JSANDS found the system to be useful, functional, and high-performing. In a previous study on the usability of JSANDS, health professionals rated it positively as indicated by the high usability ratings, satisfaction with the system, and ratings of the helpfulness of the system in making important decisions with quality of care [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The five hospitals, including one university teaching hospital, three public hospitals, and one private hospital, were selected for pilot testing of the JSANDS. The criteria for the selection of hospitals and JSANDS usability and functionality were described in previous studies [17,19,20]. The sociodemographic and obstetric characteristics of Jordanian and Syrian women and their birth outcomes were retrieved from JSANDS and compared.…”
Section: Methodsmentioning
confidence: 99%
“…The Jordan Stillbirths and Neonatal Deaths Surveillance System (JSANDS) is an electronically secure surveillance system to register and disseminate reliable, comprehensive, individual-level data on stillbirths and neonatal deaths, the causes and the risk factors most commonly associated with perinatal mortality in Jordan [16][17][18]. The system record events for women prospectively after giving their births.…”
Section: Introductionmentioning
confidence: 99%